The communist manifesto now : socialist register 1998 - Leys, Colin; Panitch, Leo. ([S.l.] : Monthly Review Press, 1998)
The central focus of The Communist Manifesto Now is the profound relevance of the famous pamphlet today. This theme is explored in essays on the relationship between the Communist Manifesto and contemporary political and democratic theory, the labor movement, feminism, the history of the left, environmentalism, and postmodernity.
Keywords: Communism; Manifest der Kommunistischen Partei (Marx, Karl); Socialism